Foreign direct investment and development : the new policy agenda for developing countries and economies in transition - Moran, Theodore H. (Institute of International Economics WashingtonUS, 1998)
Focuses initially on host-country policies that attempt to shape foreign investor activities especially investment promotion, domestic-content requirements, and export-performance requirements. Looks at host-country policies that attempt to constrain ownership on the part of foreign direct investors, in particular, joint-venture mandates and technology-licensing requirements. Examines special problems of host-country policies toward natural-resource and private-infrastructure investments. Conclude with a 'new agenda' of policy recommendations that addresses each of these individual areas of policy debate and then weaves them together in a structure that might take the form of a new international agreement on investmetn within the World Trade Organization.